Psychotic-Like Experiences: A Challenge in Definition and Assessment - Hinterbuchinger, Barbara; Mossaheb, Nilufar (Frontiers in Psychiatry, 2021)
Assuming a continuum between psychotic experiences and psychotic symptoms aligned between healthy individuals and patients with non-psychotic and psychotic disorders, recent research has focused on subclinical psychotic experiences. The wide variety of definitions, assessment tools and concepts of psychotic-like experiences (PLEs) might contribute to the mixed findings concerning prevalence and persistence rates and clinical impact. In this narrative review, we address the panoply of terminology, definitions and assessment tools of PLEs and associated concerns with this multitude. Moreover, the ambiguous results of previous studies regarding the clinical relevance of PLEs are described. In conclusion, we address clinical implications and highly suggest conceptual clarity and consensus concerning the terminology and definition of PLE. The development of an agreed upon use of a “gold standard” assessment tool seems essential for more comparable findings in future research.